Rescue of the MERTK phagocytic defect in a human iPSC disease model using translational read-through inducing drugs - Conor M. Ramsden (Nature Portfolio, 2017)
Abstract Inherited retinal dystrophies are an important cause of blindness, for which currently there are no effective treatments. In order to study this heterogeneous group of diseases, adequate disease models are required in order to better understand pathology and to test potential therapies. Induced pluripotent stem cells offer a new way to recapitulate patient specific diseases in vitro, providing an almost limitless amount of material to study. We used fibroblast-derived induced pluripotent stem cells to generate retinal pigment epithelium (RPE) from an individual suffering from retinitis pigmentosa associated with biallelic variants in MERTK. MERTK has an essential role in phagocytosis, one of the major functions of the RPE. The MERTK deficiency in this individual results from a nonsense variant and so the MERTK-RPE cells were subsequently treated with two translational readthrough inducing drugs (G418 & PTC124) to investigate potential restoration of expression of the affected gene and production of a full-length protein. The data show that PTC124 was able to reinstate phagocytosis of labeled photoreceptor outer segments at a reduced, but significant level. These findings represent a confirmation of the usefulness of iPSC derived disease specific models in investigating the pathogenesis and screening potential treatments for these rare blinding disorders.